Value-Added Tax : Administrative and Policy Issues - Tait, Alan (Occasional Papers; Occasional Paper ;, 1991)
More than 50 countries worldwide employ a value-added tax. What are its effects on prices, exports, and investment? Is it regressive? These and other questions are answered in this collection of papers presented at a March 1990 Jakarta seminar on the VAT in Asia.